Bridging the Conventions: Effects of Modular Approach In Teaching Elementary Grades - Abaya, Leomar M.; Dela Cruz, Joangelette; Llobera, Clarence (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study described and examined the delivery, effectiveness and efficiency of modular approach in teaching among the Pandi Heights Elementary School and Akle Elementary Schools both of which were within the auspices of Schools Division of Bulacan. There were 54 teachers served as the respondents of the study. They were given survey questionnaire which was administered and retrieved through google forms. Results revealed that utilization of modular approach was significant and contributory to achieve meaningful learning in order to achieve efficient delivery of learning competencies and skills were honed independently based from the acquired learning experiences of learners. Thus, the findings showed that the schools were able to provide and assist teachers in module preparation and expenses. Apparently, there were personal expenses made by the teachers to supplement the reproduction of modules, financial support of the school was found significant to prepare and reproduce the modules. Further, proper evaluation to teachers’ instructional competence was made in order to monitor the checking and assessment of learners’ outputs contained in their modules. . Profile of the respondents in terms of age, highest educational attainment and number of years in teaching were positively correlated with the delivery and effectiveness of modular approach in teaching elementary grades.